The integration of contact by impact verbs into the intransitive motion construction - Iza, Aneider (Círculo de Lingüística Aplicada a la Comunicación, 2015)
The present investigation will analyze the lexical-constructional integration of contact by impact verbs (transitive by origin) into the intransitive-motion construction. Departing from the classical works by Levin (1993), Goldberg (1995) and Faber and Mairal (1999) on contact by impact verbs, I will propose a new taxonomy that overcomes the weaknesses of previous classifications and discuss the constructional use of these verbs in real language data. Finally, I will explain the compatibility of such verbs with the intransitive-motion construction following the explanatory tools provided by the Lexical Constructional Model (Ruiz de Mendoza and Mairal, 2008a, 2008b, 2011). The main conclusions that derive from this study are that most contact-by-impact verbs are compatible with the intransitive-motion construction, this integration being possible by applying different high-level metaphors and metonymies and that all contact-by-impact verbs that are related to sound (batter, bump, crack,…) are licensed into the intransitive-motion construction thanks to the use of the high-level metonymy RESULT FOR ACTION, in which the resulting sound is taken as the action performed by the subject.